2015
DOI: 10.1016/j.jbi.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

On the creation of a clinical gold standard corpus in Spanish: Mining adverse drug reactions

Abstract: The advances achieved in Natural Language Processing make it possible to automatically mine information from electronically created documents. Many Natural Language Processing methods that extract information from texts make use of annotated corpora, but these are scarce in the clinical domain due to legal and ethical issues. In this paper we present the creation of the IxaMed-GS gold standard composed of real electronic health records written in Spanish and manually annotated by experts in pharmacology and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 33 publications
0
59
0
1
Order By: Relevance
“…For example, Albright et al (2013) achieved an F1 measure of 0.697 in exact match, but of 0.750 in partial match. Overall, our Ogren et al (2008) for English (from 75.7 to 81.4% in entity annotation, exact match) and Oronoz et al (2015) for Spanish (from 88.63 to 90.53% in term annotation). In a POS annotation task of clinical texts, Savkov et al (2016) also obtained similar results (0.76% of F-measure).…”
Section: Inter-annotator Agreement (Iaa)mentioning
confidence: 63%
See 1 more Smart Citation
“…For example, Albright et al (2013) achieved an F1 measure of 0.697 in exact match, but of 0.750 in partial match. Overall, our Ogren et al (2008) for English (from 75.7 to 81.4% in entity annotation, exact match) and Oronoz et al (2015) for Spanish (from 88.63 to 90.53% in term annotation). In a POS annotation task of clinical texts, Savkov et al (2016) also obtained similar results (0.76% of F-measure).…”
Section: Inter-annotator Agreement (Iaa)mentioning
confidence: 63%
“…Notable research initiatives, in collaboration with health institutions, have annotated clinical texts: the Mayo Clinic corpus (Ogren et al 2008), the Clinical E-Science Framework (CLEF) (Roberts et al 2009), the THYME (Temporal Histories of Your Medical Events) project (Styler et al 2014), 7 the SHARP Template Annotations (Savova et al 2012), the MiPACQ (Multi-source Integrated Platform for Answering Clinical Questions) (Albright et al 2013), the IxA-Med-GS (Oronoz et al 2015) or the Harvey corpus (Savkov et al 2016). Research challenges have also fuelled the annotation of resources or enrichment of available texts.…”
Section: Introductionmentioning
confidence: 99%
“…for English (Uzuner et al, 2011;Pradhan et al, 2013Pradhan et al, , 2014, for Swedish (Skeppstedt et al, 2014), for French (Névéol et al, 2015), for Polish (Mykowiecka et al, 2009) and for German (Roller et al, 2016). Oronoz et al (2015) …”
Section: Previous Workmentioning
confidence: 99%
“…In Spanish clinical domain, (Oronoz et al, 2015) reported that 27.58% of diseases presented in a corpus of electronic health records are negated. Although this percentage is not directly comparable with the percentage of negated sentences shown in Table 2, the numbers seem similar.…”
Section: Negation In Spanish Clinical Textsmentioning
confidence: 99%
“…Although the authors mention that 500 medical texts have been manually annotated, they do not provide more information about this goldstandard. Oronoz et al (2015), annotated negated adverse drug reactions, but they did not annotate the words expressing negation. The negation was annotated as a modifier of the disorder or drug.…”
Section: Introductionmentioning
confidence: 99%